Epistemic trust and associations with psychopathology: Validation of the German version of the Epistemic Trust, Mistrust and Credulity-Questionnaire (ETMCQ). - Anna-Maria Weiland; Svenja Taubner; Max Zettl; Leonie C Bartmann; Nina Frohn; Mirijam Luginsland; Jana Volkert (PLoS ONE)
Epistemic trust, defined as trust in socially transmitted knowledge, is discussed as a psychopathological factor in the context of new transdiagnostic approaches for the assessment of mental disorders. The aim of this study is to test the factorial, convergent, and discriminant validity of the German version of the new Epistemic Trust, Mistrust and Credulity-Questionnaire (ETMCQ). Data were collected cross-sectionally from the German-speaking general population (N = 584) and in a second sample of clinical (n = 30) and non-clinical (n = 30) participants. The previously proposed three-factor structure of the ETMCQ was analyzed using confirmatory factor analysis. The ETMCQ's ability to differentiate between clinical and non-clinical participants was tested with t-tests. Correlations with early childhood trauma, maladaptive personality traits, and impairments in personality functioning were examined. The relationship between epistemic trust and mentalization was analyzed in a structural equation model. Regarding the factorial validity, the model fit of the originally proposed ETMCQ proved to be insufficient. The model fit to the data was good for a shortened 12-item version. The study was unable to identify any significant differences between clinical and non-clinical participants. For mistrust and credulity, correlations with associated constructs supported their construct validity. However, the results for the trust subscale were heterogeneous. The study offers initial empirical support for a revised 12-item self-report measure of epistemic trust and for the link between mistrust and credulity with markers of psychopathology. Further investigation of the ETMCQ and its psychometric properties, as well as research on integration of epistemic trust into new, transdiagnostic approaches to psychopathology is needed.